Prevalence of Lyme Disease Attributable to Military Service at the USMA, West Point NY: FY2016–2018 - Schubert, Sara L; Melanson, Vanessa R (Military medicine, 2020)
Abstract Introduction Lyme disease incidence rates have steadily increased since its official recognition in 1975. Since exposure to Lyme is associated with activities conducted in and around tick-habitats including tall grass, shrubs, deciduous forest, and leaf litter, it has been suggested that service members, who are thought to spend higher amounts of time in these habitats due to training requirements, may have higher risk for exposure. Specifically, this study looks at service member and family member exposure to Ixodes scapularis, the vector for Lyme in the Northeastern and Midwestern United States. While literature pertaining to occupational and military specific exposures to Lyme vectors have attempted to quantify the possible elevated risk of Lyme disease for service members, thus far, studies have not consistently confirmed that service members are at a greater risk than family members. Materials and Methods This cross-sectional study looks at cases of Lyme disease at Keller Army Community Hospital (KACH) on the West Point Military Reservation in New York during Fiscal Year (FY) 2016 through FY2018. Lyme cases were pulled from Military Health System Mart using current ICD-10-CM codes for Lyme related conditions (A69.20 and A69.29). In total, 144 cases were considered for the analysis. Totaling all service members and family members enrolled at KACH over the three-year period account for 35,526 person-years. Period prevalence, attributable risk percentage, population attributable risk percentage, and corresponding 95% confidence intervals were calculated for service members and family member categories. This study was conducted on human subject research according to 32CFR219 and meets the requirements of exempt status under 32CFR219.101(b)(4) because it is a cross-sectional study on existing de-identified patient data. Results During FY2016-2018, service members accounted for 63 cases of Lyme totaling 21,595 person-years with a period prevalence of 292 cases per 100,000 (219.8, 363.7). Family members accounted for 81 cases with a total of 13,931 person-years with a period prevalence of 581 cases per 100,000 (455.2, 707.7). The percentage of attributable risk during the three-year period credited to military status is −99.30% (−145.69%, −52.91%). The population attributable risk percentage is −43.4%. Conclusions While this study was unable to capture the military specific occupational exposure to I. scapularis, it does show a difference in period prevalence between service members and family members with the family members being at higher risk to contract Lyme instead of service members as is commonly suggested in the literature. Additional studies may be conducted to see if this holds true across service member Military Occupational Specialties as a proxy for occupational exposure. Similar studies should be conducted at military installations situated in Lyme endemic areas to determine if these results are comparable across the military or specific to West Point. Future research should attempt to identify all the service member protective factors against Lyme with attribution to permethrin-treated uniforms and other military interventions designed to defend soldiers against vector-borne diseases.